The chemical enrichment in the early Universe as probed by JWST via direct metallicity measurements at z ∼ 8. Issue 1 (27th September 2022) - Curti, Mirko; D'Eugenio, Francesco; Carniani, Stefano; Maiolino, Roberto; Sandles, Lester; Witstok, Joris; Baker, William M; Bennett, Jake S; Piotrowska, Joanna M; Tacchella, Sandro; Charlot, Stephane; Nakajima, Kimihiko; et al.
ABSTRACT: We analyse the chemical properties of three z∼ 8 galaxies behind the galaxy cluster SMACS J0723.3-7327, observed as part of the Early Release Observations programme of the James Webb Space Telescope . Exploiting [O iii ]λ4363 auroral line detections in NIRSpec spectra, we robustly apply the direct T e  method for the very first time at such high redshift, measuring metallicities ranging from extremely metal poor (12 + log(O/H)≈ 7) to about one-third solar. We also discuss the excitation properties of these sources, and compare them with local strong-line metallicity calibrations. We find that none of the considered diagnostics match simultaneously the observed relations between metallicity and strong-line ratios for the three sources, implying that a proper re-assessment of the calibrations may be needed at these redshifts. On the mass–metallicity plane, the two galaxies at z ∼ 7.6 ($\rm log(M_*/M_{\odot }) = 8.1, 8.7$ ) have metallicities that are consistent with the extrapolation of the mass–metallicity relation at z ∼2–3, while the least massive galaxy at z ∼ 8.5 ($\rm log(M_*/M_{\odot }) = 7.8$ ) shows instead a significantly lower metallicity. The three galaxies show different level of offset relative to the Fundamental Metallicity Relation, with two of them (at z ∼ 7.6) being marginally consistent, while the z ∼ 8.5 source deviating significantly, being probably far from the smooth equilibrium between gas flows, star formation, and metal enrichment in place at later epochs.